Autophagy is not uniformly cytoprotective: a personalized medicine approach for autophagy inhibition as a therapeutic strategy in non-small cell lung cancer - Saleh, Tareq; Cuttino, Laurie; Gewirtz, David A. (Biochimica et biophysica acta, 2016)
Lung cancer is the leading cause of cancer-related death worldwide. In addition to surgical resection, which is considered first-line treatment at early stages of the disease, chemotherapy and radiation are widely used when the disease is advanced. Of multiple responses that may occur in the tumor cells in response to cancer therapy, the functional importance of autophagy remains equivocal; this is likely to restrict current efforts to sensitize this malignancy to chemotherapy and/or radiation by pharmacological interference with the autophagic response. In this review, we attempt to summarize the current state of knowledge based on studies that evaluated the function of autophagy in non-small cell lung cancer (NSCLC) cells in response to radiation and the most commonly used chemotherapeutic agents. In addition to the expected prosurvival function of autophagy, where autophagy inhibition enhances the response to therapy, autophagy appears also to have a “non-cytoprotective” function, where autophagy blockade does not affect cell viability, clonogenicity or tumor volume in response to therapy. In other cases, autophagy may actually mediate drug action via expression of its cytotoxic function. These observations emphasize the complexity of autophagy function when examined in different tumor cell lines and in response to different chemotherapeutic agents. A more in-depth understanding of the conditions that promote the unique functions of autophagy is required in order to translate preclinical findings of autophagy inhibition to the clinic for the purpose of improving patient response to chemotherapy and radiation. •Autophagy induced by chemotherapy or radiation in non-small cell lung cancer can be protective, cytotoxic or nonprotective.•It is premature to expect that autophagy inhibition will lead to sensitization to any particular form of therapy.•The outcome of current clinical trials may erroneously indicate that this therapeutic strategy is untenable.•Biomarkers of cytoprotective autophagy must be identified in order for autophagy to become a viable clinical strategy.